Stability of dolomite under extreme heating condition : comparison between Perlis and Ipoh dolomite - Farizul Hafiz, Kasim; Mohd Nazry, Salleh; Suhardy, Daud; Saiful Azhar, Saad (Malaysian Institute for Nuclear Technology Research (MINT), Xapp Malaysia-MNS & Universiti Kebangsaan Malaysia (UKM), 2008)
Organized by Malaysian Institute for Nuclear Technology Research (MINT), Xapp Malaysia-MNS & Universiti Kebangsaan Malaysia (UKM), 29th – 30th November 2006 at Palm Garden Hotel IOI Resort, Putrajaya, Malaysia.